Mobile health: Is your next rehabilitation’s specialist in your pocket? - Kim Daniels; Farooq Azam Rathore; Bruno Bonnechère (Journal of the Pakistan Medical Association, 2024)
The past few decades have witnessed an unprecedented surge in health-related mobile applications. However, most of these applications primarily focus on lifestyle domains such as sleep, fitness, and nutrition. A notable stride in this landscape involves the emergence of applications catering specifically to rehabilitation needs. This expert review aims to provide an encompassing overview of the wide spectrum of apps available for both assessment and rehabilitation. It delves into the existing constraints associated with these tools and deliberates on the potential avenues for future advancements and integration for future advancements and integration. The transformative potential of this mobile, affordable, and user-friendly technology in reshaping the field of rehabilitation sciences will be highlighted. This article underscores how harnessing these innovations can elevate accessibility and effectiveness in the rehabilitation processes, leading to improved overall outcomes and wellbeing. Keywords: mHealth, rehabilitation, smartphone, technology, telerehabilitation, mobile applications